The role of galectin-3 in the development of idiopathic pulmonary fibrosis - Parmar, Nimesh (2019)
Introduction Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive lung disease with a poor prognosis.Currently there is no cure for IPF but there are two licenced therapeutic drugs which can only slow down the progression of fibrosis.Transforming growth factor b(TGFβ) plays a crucial role in the pathogenesis of IPF.The b-galactoside binding lectingalectin-3 promotesfibrosis through modifying the activity of TGFβ.However, the precise mechanismof galectin-3 promoting fibrosiscurrently unknown.A galectin-3 inhibitor (TD139) is currently in clinical trials for the treatment of IPF. Additionally, galectin-3 is thought to play an important role in TGFβsignalling, where loss of galectin-3 in cell prevents TGFβinduced effects. The mechanism of this is also unclear.